2021
DOI: 10.3390/ijms222011035
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells and Extracellular Vesicles in Osteosarcoma Pathogenesis and Therapy

Abstract: Osteosarcoma (OS) is an aggressive bone tumor that mainly affects children and adolescents. OS has a strong tendency to relapse and metastasize, resulting in poor prognosis and survival. The high heterogeneity and genetic complexity of OS make it challenging to identify new therapeutic targets. Mesenchymal stem cells (MSCs) are multipotent stem cells that can differentiate into adipocytes, osteoblasts, or chondroblasts. OS is thought to originate at some stage in the differentiation process of MSC to pre-osteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 103 publications
0
29
0
Order By: Relevance
“…In the TME, the effect of MSCs on tumor cells is largely dependent on the cytokines secreted by MSCs. Studies have shown that these cytokines can stimulate tumor cells leading to tumor development and metastasis by promoting migration and immune escape [ 20 , 21 ]. In osteosarcoma cells, cytokine release is considered as a biomarker of tumor progression [ 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the TME, the effect of MSCs on tumor cells is largely dependent on the cytokines secreted by MSCs. Studies have shown that these cytokines can stimulate tumor cells leading to tumor development and metastasis by promoting migration and immune escape [ 20 , 21 ]. In osteosarcoma cells, cytokine release is considered as a biomarker of tumor progression [ 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that EVs secreted by MSCs have similar therapeutic effects on MSCs because some of the paracrine effects of MSCs are derived from exosomes, and most of the therapeutic effects of MSCs are responsible for the paracrine effects of EVs in certain diseases via miRNAs, mRNAs, and proteins as functional molecules [ 212 , 213 , 214 , 215 ].…”
Section: Therapy Via Msc-derived Evs As a Novel Dds Systemmentioning
confidence: 99%
“…Futuristic line of cancer treatment focusing on tumor microenvironment with/using modified mesenchymal stem cells. miRNA profiling from circulating sEVs is equivalent to sEVs profiling from tissue (170)(171)(172). Tumor-derived sEVs in the peripheral circulation exhibit different miRNA expression patterns than healthy person sEVs.…”
Section: Role Of Stem Cells Derived Evs In Cancer Progressionmentioning
confidence: 99%